Evaluation of wettability characteristics and adhesion of resin composite to photo-polymerized pulp-capping materials with and without bioactive glass - Tulumbaci, Fatih; Korkut, Emre; Ozer, Hazal; Özcan, Mutlu (Brazilian Dental Science, 2019)
Objective: The purpose of this study was to evaluate mechanical and physical properties of three different light-curable resin-based materials (TheraCal LC, Biner LC, and CalciPlus LC) with or without BAG. Material and Methods: 15 cylindrically shaped specimens (n=5) were prepared for contact angle test. The test values (?) were determined with the sessile drop method using three test liquids. 30 acrylic cylindrical blocks were prepared, and holes of (6mmx1mm) were made in the center of the cylinders for shear bond strength test. An adhesive system and a restorative composite material were applied via cylindrically shaped plastic tubes of (2mmx2mm) at the center of the light-curable resin-based material surfaces. The specimens were mounted in a universal testing machine. A crosshead speed of 1 mm/min was applied to each specimen using a knife-edge blade. Results: The highest (74.77°±13.56) and the lowest (35.35°±12.89) contact angle values were recorded for the MB Biner LC group and the CalciPlus LC, respectively. Statistically significant differences observed in contact angle values between the test groups (p